MHD micropolar nanofluid flow over an exponentially stretching/shrinking surface: triple solutions - Dero, Sumera; Mohd Rohni, Azizah; Saaban, Azizan (Akademia Baru Publishing (M) Sdn Bhd, 2019)
In this study, the problem of MHD micropolar nanofluid boundary layer flows over an exponentially stretching/shrinking sheet with radiation and suction effect is considered. The Buongiorno’s nanofluid model is applied to the problem. The governing equations are first transformed to the coupled nonlinear similarity equations by using similarity transformations. The resulting equations which is in ordinary differential equations form are then solved numerically by using shooting method.Triple solutions are observed to exist for the flows. A comparison with existing solutions in literature for specific case are made to assess the accuracy of the present results. Further, the flows profiles are examined, and it is found that the presence of suction parameter will contribute the occurrences of triple solutions.